Evaluation of digital collections user interfaces - Vrana, Radovan (Array, 2009)
Digital information resources play a very important role in today’ s world. They eliminate or reduce prior constraints of distance, fragility of resources, or limited physical access to resources premises a freedom and flexibility in information access unprecedented in human history (Bates, 2002). Their existence would be impossible without information systems that enable their functioning. The life cycle of an information system consists of the standard sequence of development phases. This sequence of development phases includes the process of evaluation or assessment of the information system. Only thorough and frequent evaluation of the information system and its components will ensure its flawless functioning. During the process of evaluation, special attention is given to user interfaces, access points to the content of online information resources. The process of evaluation can be carried out by application of several different methods. This paper puts focus on selected methods for evaluation of information systems and their user interfaces that can be also applied to digital collections (and their user interfaces) available on the Internet. It also presents results from the research of the Croatian national heritage digital collections available on the Internet and common characteristics of their user interfaces.